Impact of obesity on the molecular response to a single bout of exercise in a preliminary human cohort. Issue 5 (26th April 2022) - Vanderboom, Patrick; Zhang, Xiaoyan; Hart, Corey R.; Kunz, Hawley E.; Gries, Kevin J.; Heppelmann, Carrie J.; Liu, Yuanhang; Dasari, Surendra; Lanza, Ian R.
Abstract: Objective: The health benefits of exercise are well documented, but several exercise‐response parameters are attenuated in individuals with obesity. The goal of this pilot study was to identify molecular mechanisms that may influence exercise response with obesity. Methods: A multi‐omics comparison of the transcriptome, proteome, and phosphoproteome in muscle from a preliminary cohort of lean individuals ( n  = 4) and individuals with obesity ( n  = 4) was performed, before and after a single bout of 30 minutes of unilateral cycling at 70% maximal oxygen uptake (VO2 peak). Mass spectrometry and RNA sequencing were used to interrogate the proteome, phosphoproteome, and transcriptome from muscle biopsy tissue. Results: The main findings are that individuals with obesity exhibited transcriptional and proteomic signatures consistent with reduced mitochondrial function, protein synthesis, and glycogen synthesis. Furthermore, individuals with obesity demonstrated markedly different transcriptional, proteomic, and phosphoproteomic responses to exercise, particularly biosynthetic pathways of glycogen synthesis and protein synthesis. Casein kinase II subunit alpha and glycogen synthase kinase‐3β signaling was identified as exercise‐response pathways that were notably altered by obesity. Conclusions: Opportunities to enhance exercise responsiveness by targeting specific molecular pathways that are disrupted in skeletal muscle from individuals with obesity await a better understanding of the precise molecular mechanisms that may limit exercise‐response pathways in obesity.